Isolation and Characterization of Alpaca Tetranucleotide Microsatellite Markers - Munyard, Kylie; Ledger, J.; Lee, C.; Babra, C.; Groth, David (Association for the Advancement of Animal Breeding and Genetics, 2009)
Hybridisation-capture was used to create 12 unique alpaca DNA libraries each enriched for a different tetranucleotide microsatellite motif. Two hundred and forty nine microsatellites were found, of which 26 were polymorphic (motifs GGAT, GTTT and GCAC). Nine markers were fully characterised on 45 samples. Allele numbers ranged from 6 (Locus P135) to 12 (loci P149 and PCTD17). There was no evidence of linkage disequilibrium (p = 0.064 - 1) or deviation from Hardy-Weinberg equilibrium (p = 1). Polymorphic information content ranged from 0.48 to 0.82. When combined, the markers had an exclusion probability of 97.7%. These markers will be useful for parentage determination (especially if combined into a multiplex) and will add to the pool of markers available for mapping of desirous or deleterious traits in alpacas.